Images on Halaf Pottery from Syria - F. Majar (Вестник Кемеровского государственного университета, 2022)
Pottery marked the advent of the agricultural revolution, transition to sedentary life, and a new era of intellectual development. Man used pottery to communicate important ideas in symbolic form. This article presents examples of ancient art, in particular, zoomorphic and anthropomorphic images on pottery. The research featured ceramic vessels found at the archaeological sites of Halaf culture in Syria. The research objective was to interpret their meaning using various descriptive and analytical methods. The author believes that the ancient potter used animal images out of reverence  or fear. Animal images on pottery point at the close interaction between people, animals, and nature.